Molecular diagnostic techniques and their potential role in stone fruit certification schemes - Pallás V.; Sanchez-Navarro J.A.; Canizares M.C. (Stone fruit viruses and certification in the Mediterranean countries: problems and prospects, 1998)
Stone fruit trees are affected by a large number of viruses that cause important economic losses. At the moment, unlike bacterial and fungal diseases, no chemical exist to be applied directly to control viral or viroid diseases. So, the early detection by means of sensitive diagnostic methods is the main way to control them. The extraordinary progress made in the nucleic acid research recently and the application of recombinat DNA technology in plant virology have permitted the use of diagnostic methods based on the genomic component of viruses and viroids. Among them, molecular hybridisation and polymerase chain reaction (PCR) have received great interest lately and have been incorporated in the diagnostic field of plant virology. This review focuses on the molecular basis of these two techniques, their application to the diagnosis of stone fruit viruses and viroids and their potential incorporation into the certification schemes.